PELATIHAN PEMANFAATAN TEKNOLOGI INFORMASI PADA MASYARAKAT DI KELURAHAN BELAKANG PADANG KECAMATAN BELAKANG PADANG KOTA BATAM - Sasa Ani Arnomo; Yuli Siyamto (ASOSIASI IDEBAHASA KEPRI, 2021)
The influence of globalization with the support of information technology is a double-edged sword. on the one hand, we cannot deny the benefits and threats it brings on the other. Thus, these benefits are also called positive effects and threats are called negative effects. The positive influence that can be felt by Information Technology is an increase in speed, accuracy and convenience. It provides efficiency in various fields, especially in terms of time, energy and costs. For example, the manifestation of Information Technology that is easily seen around us is email where sending a letter only takes a short time. Information technology is also utilized in the field of economic activities such as E-banking, E-commerce, e-shopping and many more. Meanwhile, the negative impact that may arise as a result of information technology is pornography, while the economic aspect of globalization is the opening of free markets that allow foreign products to enter easily. The large number of foreign products and the addition of relatively cheaper prices can reduce the attractiveness of domestic products. This is a big challenge for SMEs in business competition. Financial fraud and embezzlement through electronic media are also rife so it is necessary to learn how to do business online. With this background, there is a need for guidance on how to deal with developments in information technology. As many as 93% of the responses from the community stated that they were very good and useful.